Serum amyloid A protein (SAA): a marker for liver allograft rejection in humans - Feussner, Giso; Stech, Christine; Dobmeyer, Jürgen; Schaefer, H.; Otto, Gerd; Ziegler, Reinhard (Journal of molecular medicine, 1994)
Serum amyloid A protein (SAA) concentrations were monitored in 12 consecutive liver transplant recipients until the 70th postoperative day. Fourteen rejection episodes were identified histologically in 42 liver biopsies of the grafts. Of 12 rejections 8 (66.7%) were characterized by pronounced simultaneous increases in SAA concentrations in plasma, the mean peak value being 16.94 ± 8.82 mg/dl (range 4.58-28.55 mg/dl) compared with a mean normal value of 0.98 ±0.42 mg/dl in healthy controls. Of 42 biopsies 28 did not show histological evidence of graft rejection. Of 25 negative biopsies 24 (96.0%) were not accompanied by a parallel SAA increase in plasma. These findings demonstrate that measurements of SAA concentrations may provide a valuable non-invasive aid in identifying acute liver allograft rejection in humans.